2005
DOI: 10.1021/bi0476432
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of the Chromophore of the asFP595 Chromoprotein from Anemonia sulcata

Abstract: A model compound for the chromophore within the purple nonfluorescent GFP-like chromoprotein asFP595 was synthesized. The postulated structure of the chromophore, 2-acetyl-4-(p-hydroxybenzylidene)-1-methyl-5-imidazolone, was taken from the high-resolution crystal structure analysis of intact asFP595 [Quillin, M. L., Anstrom, D., Shu, X., O'Leary, S., Kallio, K., Lukyanov, K. A., and Remington, S. J. (2005) Kindling Fluorescent Protein from Anemonia sulcata: Dark-State Structure at 1.38 A Resolution, Biochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
1
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(117 citation statements)
references
References 29 publications
9
105
1
2
Order By: Relevance
“…Thus, DMF appears to be close to the chromophore environment within Kaede protein, which has emission maximum at 582 nm [10]. Earlier, the same similarity between spectra of synthetic chromophore in basic DMF and native protein was found for asFP595 [28]. In contrast to other Kaede-like chromophores as well as GFP and asFP595 chromophores, HYG emission spectrum contained a shoulder at 620-640 nm which is separated from the main peak very clearly (Fig.…”
Section: Spectral Propertiessupporting
confidence: 64%
See 2 more Smart Citations
“…Thus, DMF appears to be close to the chromophore environment within Kaede protein, which has emission maximum at 582 nm [10]. Earlier, the same similarity between spectra of synthetic chromophore in basic DMF and native protein was found for asFP595 [28]. In contrast to other Kaede-like chromophores as well as GFP and asFP595 chromophores, HYG emission spectrum contained a shoulder at 620-640 nm which is separated from the main peak very clearly (Fig.…”
Section: Spectral Propertiessupporting
confidence: 64%
“…All Kaede-like chromophores in basic DMF and DMSO demonstrated a well-detectable red fluorescence with a quantum yield well above that of HBMPI, HBMPDI [27], and GFP and asFP595 chromophores [22,28] (Table 2 and Fig. 4).…”
Section: Spectral Propertiesmentioning
confidence: 96%
See 1 more Smart Citation
“…asFP595 wild-type protein contains 100% cleaved chromophore form and is characterized with molar extinction coefficient at 567 nm of 150,000 M À 1 cm À 1 (ref. 22). Absorbance of alkali-denatured asFP595 chromophore at 380 nm is 47% of asFP595 absorption at 567 nm at pH 7.5 and thus was determined as 70,000 M À 1 cm À 1 .…”
Section: Fluorescent Proteins Characterization In Vitromentioning
confidence: 99%
“…1b). Increasing I b and I y can, in principle, cut down the fluorescence settling time to that of the actual molecular switch [i.e., Ï·100 ps (18,19)], but at the low intensities used in our study, the observed fluorescence settling time reflects the population kinetics of the states. Four challenges in using asFP595 become apparent: (i) the signal is rather noisy because of the Ïœ1% fluorescence quantum yield of asFP595 (19); (ii) switching off by blue light is incomplete; (iii) repeated cycling is accompanied with photobleaching; (iv) in an imaging system, the applied intensities have to be adapted to the pixel recording time because they determine the fluorescence settling.…”
Section: Resultsmentioning
confidence: 99%